How is carbonate crust digested by magma? - Borisova, Anastassia Y.; Bohrson, Wendy A. (Frontiers in Earth Science, 2023)
A magma's volatile budget depends on deep magmatic sources, degree of differentiation and degassing conditions, and on volatile input from assimilated crust. It is, therefore, important to know the exact mechanism by which crust is assimilated into magma to understand volatile budgets and eruption behavior. To explore reactions between carbonate, calc-silicate or skarn xenoliths and basaltic andesite magma, we studied ten calc-silicate xenoliths from the 1994, 1998, 2006 and 2010 Merapi eruptions and four sediment samples of local Javanese carbonate crust. In situ electron probe microanalysis of the 1994 -2010 calc-silicate xenolith minerals and glasses suggests that calcite is a minor and metastable mineral phase in association with wollastonite. In addition, carbonate melts quenched to calcic glasses (32 ± 7 wt. % SiO2, 38 ± 3 wt.% CaO), similar to experimental glasses produced by crust-melt interaction experiments. Thermodynamic modeling using rhyolite MELTS (version 1.2.0) predicts production of highly silicic melts (up to ~84 wt.% of SiO2) and CaO rich (up to ~25 wt. %) during partial melting of calc-silicate material. The observed mechanism of calc-silicate xenolith assimilation is generation of highly silicic (77 ± 4 wt.% of SiO2) melts in association with idiomorphic diopside (Wo49En29; 57 ± 3 Mg# = Mg/(Mg+Fe 2+ )) and other calcic pyroxenes (Wo54-82 En2-21; 16 -43 Mg#) due to xenolith partial melting and incongruent dissolution reactions. We hypothesize that the rate-limiting process is the subsequent mixing of the produced crustal melts with representative resident andesitic melt (average 65 wt.% SiO2) through chemical diffusion, which explains major and volatile (Cl) element contents in the Merapi glass products. The disequilibrium process of calc-silicate crustal assimilation can thus be well predicted by dissolution experiments and thermodynamic modelling using rhyolite-MELTS or Magma Chamber Simulator (MCS). The rate of calc-silicate crustal assimilation is still unconstrained without adequate high-temperature kinetic time-series experiments. We predict that the crustal assimilation rate is controlled by the Si-Al diffusion and associated convection in the hydrous silicate magma.